2018
DOI: 10.1053/j.jrn.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Dose for Hemodialysis Patients: Where to Begin? Results from a Prospective Cohort Study

Abstract: Engaging in physical activity is associated with decreased mortality risk among hemodialysis patients. Our findings of a substantial mortality benefit among those who engage in at least 4,000 steps provide a basis for as a minimum initial recommendation kidney health providers can provide for mobility disability-free hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 43 publications
(42 reference statements)
1
43
1
1
Order By: Relevance
“…Although the current guidelines for MHD patients recommend moderate-intensity exercise, many patients at our centers are unable to tolerate this level of intensity. Based on evidence suggesting that a mere increase in physical activity can elicit meaningful long-term clinical and performance benefits [16,17], we developed a lowintensity exercise program and prolonged the study duration to 2 years. We further created an easy-to-follow video for the patients and devised exercises that would require no equipment beyond hand and ankle weights, with the aim of creating a cost-effective, safe, and easily implemented exercise program.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although the current guidelines for MHD patients recommend moderate-intensity exercise, many patients at our centers are unable to tolerate this level of intensity. Based on evidence suggesting that a mere increase in physical activity can elicit meaningful long-term clinical and performance benefits [16,17], we developed a lowintensity exercise program and prolonged the study duration to 2 years. We further created an easy-to-follow video for the patients and devised exercises that would require no equipment beyond hand and ankle weights, with the aim of creating a cost-effective, safe, and easily implemented exercise program.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The results of our series showed an average age of 54.6 years, with extremes ranging from 18 to 85 years [4,7]. Several series in the literature report a predominance of men, notably a local Moroccan study carried out by Karimi [8] at the Al Fârâbî hospital in Oujda with a sex ratio of 45H / 38F, that of Fiaccadorie [9] carried out in Italy with a percentage of 67% male, and that of Matsuzawa [10] in Japan had a male predominance of 55%. This joins our study where the male sex is predominant with a percentage of 60%.…”
Section: Low Physical Activity Risk Factorsmentioning
confidence: 85%
“…A study of 282 stable HD patients who were able to walk without assistance, found that walking less than 4000 steps per nondialysis day at baseline (four assessments over 1 week) was associated with a 2.4 fold higher adjusted mortality (over a 56 month median follow-up) compared with that in more active walkers. 16 A study of olfaction included 100 dialysis patients (94 on HD) and 25 controls. Dialysis patients had a lower mean odor identification score than controls (67% vs 84%) as well as a higher odor threshold.…”
Section: Reanalysis Of Data On 3762 Hd Patients From a 3-year Prospecmentioning
confidence: 99%
“…A study of 282 stable HD patients who were able to walk without assistance, found that walking less than 4000 steps per nondialysis day at baseline (four assessments over 1 week) was associated with a 2.4 fold higher adjusted mortality (over a 56 month median follow‐up) compared with that in more active walkers …”
mentioning
confidence: 99%